2013
DOI: 10.1097/ccm.0b013e31828a435f
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Evidence-Informed Practices for Patient Care Rounds in the ICU*

Abstract: Although the evidence base for best practices of patient care rounds in the ICU is limited, several practical and low-risk practices can be considered for implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 58 publications
2
106
0
Order By: Relevance
“…Studies reported short and long-term psychological effects on patients of being in an ICU [16,17]. Short-term effects usually relate to the patient within ICU and for 2 to 3 days after transfer [16], whereas long-term effects have been reported up to 2 years after an ICU stay [15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported short and long-term psychological effects on patients of being in an ICU [16,17]. Short-term effects usually relate to the patient within ICU and for 2 to 3 days after transfer [16], whereas long-term effects have been reported up to 2 years after an ICU stay [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bhamidipati et al 32 conducted a systematic review to identify the structure and outcomes of interdisciplinary rounds on medical wards while Lane et al 60 included studies of BR while attempting to identify best practices for patient care rounds in the ICU. However, both of these reviews included relatively few studies focusing on BR.…”
Section: Discussionmentioning
confidence: 99%
“…However, the system processes that are involved in the delivery of care are only one facet of several that affect the delivery of quality care (de Souza et al, 2012). Attention should also be focused on human factors, such as interprofessional teamwork and the processes by which information is transmitted, evaluated, and acted on, as these factors can have a significant impact on the process of care (Alvarez and Coiera, 2005;Collins et al, 2011;Dong et al, 2011;Lane et al, 2013).…”
Section: Introductionmentioning
confidence: 99%